Day 2 Tue, October 07, 2014 2014
DOI: 10.2118/171346-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Stress Calculations for Sucker Rod Pumping Systems

Abstract: Preventing stress related failures is an essential part of optimizing your sucker rod pumped well. Tracking the maximum and minimum rod stress along with appropriate pump off control can ensure longer life for the rods and the entire sucker-rod pumping system.Traditionally, stress is only computed at the top of each taper. However, when stress failures occur, they happen in areas of high friction and stress which might not necessarily be near the top of the taper and therefore undetectable through traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Many scientists have used the work of Gibbs as a basis for their research [27], who have reported valuable results. The standard solution method is the finite difference method [26], [28], [29], [30], [31], [32], [33], [34]. The here shown model uses the finite differences method to solve the viscous damped wave equation.…”
Section: Downhole Systemmentioning
confidence: 99%
“…Many scientists have used the work of Gibbs as a basis for their research [27], who have reported valuable results. The standard solution method is the finite difference method [26], [28], [29], [30], [31], [32], [33], [34]. The here shown model uses the finite differences method to solve the viscous damped wave equation.…”
Section: Downhole Systemmentioning
confidence: 99%
“…The interaction forces between sucker rod string and tubing, F 1 , are within 1.5% of the rod weights based on the statistic data for the producing CBM wells. And the semi-dry friction forces between the plunger and pump barrel, F 2 , can be approximately determined by the formulae [24,25]. And the friction forces, F 3 , are caused by the rod string and well liquid during the downstroke period [26].…”
Section: Design Calculation Of Friction Loadingsmentioning
confidence: 99%
“…Experimental and field analysis of sucker rod pumps have also been conducted to evaluate the importance of some factors on sucker rod performance and failure. Podio et al (2003) presented results for tests with a sucker rod pump model in the laboratory to provide information on dynamic and static pump friction measurement. They reasoned that one of the major costs during production is the lifting cost.…”
Section: Introductionmentioning
confidence: 99%